2015
DOI: 10.1038/ncomms7353
|View full text |Cite
|
Sign up to set email alerts
|

Deltex1 antagonizes HIF-1α and sustains the stability of regulatory T cells in vivo

Abstract: Application of regulatory T cells (Tregs) in transplantation, autoimmunity and allergy has been extensively explored, but how Foxp3 and Treg stability is regulated in vivo is incompletely understood. Here, we identify a requirement for Deltex1 (DTX1), a contributor to T-cell anergy and Foxp3 protein level maintenance in vivo. Dtx1−/− Tregs are as effective as WT Tregs in the inhibition of CD4+CD25− T-cell activation in vitro. However, the suppressive ability of Dtx1−/− Tregs is greatly impaired in vivo. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 64 publications
5
46
0
3
Order By: Relevance
“…In addition to driving expression of T H 17 signature genes, HIF-1α also inhibited differentiation of iT reg by binding to Foxp3 through a n-terminal domain resulting in proteosomal degradation of Foxp3 in spite of TGF-β signaling present in in vitro T H 17 culture conditions [23]. Additional studies by several groups in human and murine models, have both supported and contradicted aspects of these initial reports [7075]. It is clear that HIF-1α can play a role in the differentiation of T H 17 versus iT reg cells.…”
Section: Regulation Of T Cell Metabolism Differentiation and Funmentioning
confidence: 99%
“…In addition to driving expression of T H 17 signature genes, HIF-1α also inhibited differentiation of iT reg by binding to Foxp3 through a n-terminal domain resulting in proteosomal degradation of Foxp3 in spite of TGF-β signaling present in in vitro T H 17 culture conditions [23]. Additional studies by several groups in human and murine models, have both supported and contradicted aspects of these initial reports [7075]. It is clear that HIF-1α can play a role in the differentiation of T H 17 versus iT reg cells.…”
Section: Regulation Of T Cell Metabolism Differentiation and Funmentioning
confidence: 99%
“…Instead, it was found to bind HIF‐1, promoting hydroxylation of proline residues. The authors also showed that DTX expression could prevent hypoxia‐induced reduction in the Foxp3 protein pool in T cells . These results do not appear at first glance to support a model for Foxp3–HIF‐1 co‐degradation via the proteasome as, in the absence of DTX1, Foxp3 protein loss was more pronounced alongside reduced HIF‐1 degradation.…”
Section: Ubiquitin E3 Ligase‐dependent Regulation Of Foxp3 and Treg Fmentioning
confidence: 93%
“…This deficiency was attributed to unstable expression of Foxp3 seen alongside the elevated HIF‐1 levels in the absence of DTX1. Importantly, the authors showed that simultaneous HIF‐1 and DTX1 deficiency in Tregs restored their in vivo Foxp3 expression level and largely corrected the inability of DTX1‐deficient Tregs to prevent colitis . Interestingly, DTX1 did not appear to drive the direct ubiquitination of HIF‐1.…”
Section: Ubiquitin E3 Ligase‐dependent Regulation Of Foxp3 and Treg Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the hematological context, DTX1 can negatively regulate T-cell activation by targeting mitogen-activated protein kinase kinase kinase 1 (MEKK1 or MAP3K) and protein kinase C Θ for degradation, 8,9 and mediate degradation of hypoxia-inducible factor-1α (HIF-1α) in regulatory T cells (Tregs). 10 However, in normal B cells and lymphomas, the function of DTX1 and the impact of mutations remain to be established. Somatic hypermutation has been predicted to aberrantly target the DTX1 gene, 11 and DTX1 mutations have previously been reported in follicular and splenic marginal zone lymphomas.…”
Section: Letters To the Editormentioning
confidence: 99%